An exploration of the impact of complex psychological trauma on violent males - Garcha, Enderdeep (2016)
This thesis explores the role of complex psychological trauma (CPT) and violence within male adult offenders. It aims to investigate the impact of CPT in better understanding the trauma-violence relationship. Chapter 1 provides an introduction to the topic of CPT and violence. Chapter 2 is a systematic review that investigates the prevalence of CPT in violent males and reviews the existing evidence for the trauma-violence relationship. This review provides some evidence for the trauma-violence relationship, finding that CPT correlated with violent outcomes. Physical neglect correctly classified violent offenders by offence status, whilst physical abuse, emotional abuse and sexual abuse were also found to be associated with violent offending. The findings regarding CPT predicting violent offending were mixed, whilst a higher percentage of studies supported the trauma- violence notion, a minority number of studies did not. The evidence for CPT predicting violent behaviour in custody was more consistently shown across studies assessing this outcome. The role of mediating and moderating factors in the trauma-violence relationship were also investigated, finding that psychopathy, age, substance misuse, genetic factors, and positive criminal thinking styles and attitudes accounted for some variances. Following this review, Chapter 3 includes a Thematic Analysis (TA) investigating forensic nursing staff’s perceptions of the impact of CPT on forensic male offenders with a diagnosis of personality disorder, particularly with regards to violent behaviour whilst detained in a mental health high-secure hospital. Nursing staff’s experiences of managing patient distress and violence were also explored. The findings illustrate that nursing staff believed patient distress and violent behaviour were associated with CPT experiences, suggesting that the impact of CPT on attachment, biological, cognitive and affective aspects of functioning during development, served to account for the difficulties that patients faced in adulthood and increased the likelihood of violence. On-going prevention strategies were found to be most important and more effective than short-term risk management steps. The management of patient distress in the context of the therapeutic relationship was illustrated as a significant component for promoting recovery and successfully managing challenging behaviours. Aspects of the secure environment that imitated abuse experiences were also perceived to significantly contribute to the occurrence of violent behaviour. Change with regards to transitioning and progressing through the system was identified to evoke trauma-related fears of moving on. The fear of moving on and its association with trauma experiences was explored in a single case study of a male violent offender with personality disorder, which is presented in Chapter 4. This chapter aimed to identify and outline the offender’s fears about transitioning from a high-secure hospital to a medium-secure unit (MSU), and understanding the factors that contributed to and maintained the client’s fears. The client’s fears were found to relate to previous-trauma related experiences, although interpersonal violence and trauma experiences in the prison environment were found to be a deep rooted aspect of the client’s concerns about moving on. Whilst the client feared being vulnerable to abuse, threat and further ‘persecution’, the fear of being unable to manage his behaviour (e.g. aggression) in response to this and cope with such potential experiences outside of the high-secure environment and subsequent consequences of not being able to cope (arrest and transfer to prison), was perceived to be a more frightening prospect. Upon exploring fears of moving on, the client’s existing cognitive-behavioural relapse prevention (RP) plan was reviewed in assisting the client to revisit skills and coping strategies that can be used to prepare and avoid high-risk situations. This work contributed to understanding the ways to best support the client in making a successful transition to a MSU. Key considerations and recommendations are made at the end of the chapter with regards to the case. Following this, Chapter 5 outlines a critique of the Coping Inventory for Stressful Situations (CISS; Endler & Parker, 1999), which was used in Chapter 4 as it provides a measure of coping with stressful, distressing or painful situations. The CISS is examined with regards to its purpose, reliability and validity in terms of its research uses. Chapter 6 provides a discussion of the thesis findings, outlining the implications of the research and providing recommendations for future research.